Evaluating the structural endurance of Bamboo Kelarai panels through the application of tensile strength testing methodologies (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The long-term performance and durability of bamboo kelarai panels are significantly governed by the mechanical properties of the individual bamboo strips that constitute their interwoven configuration. This research is intended to assess the durability of bamboo kelarai panels through a detailed examination of the influence of moisture content and boron-based preservation treatment on their tensile strength characteristics. An experimental laboratory methodology was implemented, employing Gigantochloa scortechinii (commonly referred to as Semantan bamboo) as the primary material, wherein the specimens were systematically classified into four distinct categories according to moisture condition (elevated and reduced) and treatment status (treated with boron and untreated). Tensile strength evaluation was carried out using a Universal Testing Machine, with peak stress values meticulously measured and documented for subsequent analytical interpretation. The findings reveal a pronounced inverse correlation between moisture content and tensile strength, whereby specimens with reduced moisture levels exhibited superior strength performance alongside greater structural stability. Furthermore, samples subjected to boron treatment demonstrated more uniform tensile behaviour, suggesting an improvement in fibre cohesion and internal structural integrity. Notably, the synergistic combination of low moisture content and boron treatment resulted in the highest recorded tensile strength values among all tested groups. Collectively, these outcomes establish a robust scientific foundation for enhancing the durability of kelarai panels through effective moisture regulation and appropriate preservation techniques, thereby contributing to the advancement of more dependable, resilient, and sustainable bamboo-based construction materials within the field of architecture.